Orthoptera of the Lena Pillars National Park (Yakutia, Russia) and adjacent territories - Ermakova, Yu. V. (Zenodo, 2022)
Ermakova, Yu. V. (2022): Orthoptera of the Lena Pillars National Park (Yakutia, Russia) and adjacent territories. Amurian Zoological Journal XIV (2): 199-211, DOI:10.33910/2686-9519-2022-14-2-199-211, URL: http://dx.doi.org/10.33910/2686-9519-2022-14-2-199-211